Konsep Moderasi Beragama Pada Pendidikan Agama Islam Dalam Perspektif Al-Qur’an Surah Al-Baqarah Ayat 143 - Ferdino, Muhammad Farhan; Razzaq, Abdur; Imron, Kristina (Jurnal Ilmiah Global Education, 2024)
Diversity in Indonesia, including language, culture, tradition and religion, often leads to conflicts due to the differences present. Therefore, progressive solutions are needed to address these issues. This study aims to understand the concept of religious moderation in Islamic Education in Indonesia, particularly as outlined in Q.S. al-Baqarah verse 143, which teaches moderation or wasathiyah. However, its application requires extra effort due to the complex challenges involved. The issues are addressed using qualitative research, with data collection methods including library research. Data is obtained from the Quranic exegesis, relevant books, and journals on moderation. The data is then analyzed using descriptive analysis techniques. The findings conclude that the concept of moderation in Q.S. al-Baqarah verse 143 is referred to as al-wasathiyah, a word that originally means "in the middle between two extremes" or "with justice, moderation, or standard." Moderation can only be manifested when four key elements are united: honesty, openness, compassion, and flexibility. In teaching Islamic religious education, teachers are expected to apply these principles by being open, a valuing all student opinions, avoiding discrimination, and being responsive and kind. Teachers should also prioritize dialogue, as positive interactions between teachers and students foster a lively and engaging classroom environment.